Case report: Adult-onset neuronal intranuclear inclusion disease with an amyotrophic lateral sclerosis phenotype - Fujita, Masako; Ueno, Tatsuya; Miki, Yasuo; Arai, Akira; Kurotaki, Hidekachi; Wakabayashi, Koichi; Tomiyama, Masahiko (Frontiers in Neuroscience, 2022)
Amyotrophic lateral sclerosis (ALS) is one of the differential diagnoses of diseases that occur in adulthood and lead to progressive generalized muscle weakness. Neuronal intranuclear inclusion disease (NIID) is a disease in which histopathologically eosinophilic nuclear inclusion bodies are found in various systems. Both familial and sporadic forms of the disease have been reported. Most cases of sporadic NIID are of the dementia type, in which the main symptom is dementia at the first onset. Familial NIID is more diverse, with the main dominant symptoms being muscle weakness (NIID-M), dementia (NIID-D), and parkinsonism (NIID-P). Furthermore, recently, a GGC-repeat expansion in the Notch 2 N-terminal like C (NOTCH2NLC) gene, which produces a toxic polyglycine-containing protein (uN2CpolyG) in patients with NIID, has also been associated with the pathogenesis of ALS. These results suggest the possibility that sporadic NIIDs may have more diverse forms. To date, no autopsy cases of NIID patients with an ALS phenotype have been reported. Here, we describe the first autopsy case report of a patient with NIID who had been clinically diagnosed with ALS. A 65-year-old Japanese man developed progressive muscle atrophy and weakness in all limbs. The patient was diagnosed with ALS (El Escoriral diagnostic criteria: probable ALS, laboratory-supported ALS). He had no cognitive dysfunction or neuropathies suggestive of NIID. He required respiratory assistance 48 months after onset. He died of pneumonia at the age of 79 years. Postmortem examinations revealed neuronal loss in the spinal anterior horns and motor cortex. In these affected regions, eosinophilic, round neuronal intranuclear inclusions were evident, which were immunopositive for ubiquitin, p62, and uN2CpolyG. No Bunina bodies or TDP-43-positive inclusions were observed in the brain or spinal cord. Our findings suggest that a small proportion of patients with NIID can manifest a clinical phenotype of ALS. Although skin biopsy is commonly used for the clinical diagnosis of NIID, it may also be useful to identify cases of NIID masquerading as ALS.